2019
DOI: 10.5858/arpa.2018-0045-rs
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Sarcoma of the Kidney

Abstract: Clear cell sarcoma of the kidney is the second most common primary renal malignancy in childhood. It is histologically diverse, making accurate diagnosis challenging in some cases. Recent molecular studies have uncovered BCOR exon 15 internal tandem duplications in most cases, and YWHAE-NUTM2 fusion in a few cases, with the remaining cases having other genetic mutations, including BCOR-CCNB3 fusion and EGFR mutations. Although clear cell sarcoma of the kidney has no specific immunophenotype, several markers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 35 publications
(40 reference statements)
0
22
0
10
Order By: Relevance
“…The classic pattern is generally noted admixed with other histopathological patterns, although the proportion varies. The most distinctive feature is the presence of fine chicken‐wire–like vasculature, which is usually not seen in other paediatric renal tumours 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The classic pattern is generally noted admixed with other histopathological patterns, although the proportion varies. The most distinctive feature is the presence of fine chicken‐wire–like vasculature, which is usually not seen in other paediatric renal tumours 4 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies into its aetiopathogenesis have identified an association with a recurrent balanced translocation t(10;17), leading to YWHAE‐NUTM2 gene fusion, in around 12% of the cases. Many other cases have shown the presence of an in‐frame internal tandem duplication of exon 15 of the BCOR gene (70% of the cases) and BCOR‐CCNB3 gene fusion; however, no association with genetic syndromes has been noted to date 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of either the YWHAE-NUTM2 gene fusion or BCOR ITD (internal tandem duplication) would be definitive for diagnosis of CCSK, 24 although cyclin D1 positivity is an acceptable alternative.…”
Section: Cell Blocks In Wtmentioning
confidence: 99%